Association physical activity and risk of major cardiovascular diseases in Chinese men and women - Bennett, D; Du, H; Clarke, R; Guo, Y; Yang, L; Bian, Z; Chen, Y; Millwood, I; Yu, C; He, P; Zheng, X; Collins, R; et al. (American Medical Association, 2017)
Importance In China, the patterns and levels of physical activity differed from those in high-income countries. Substantial uncertainty remains about the relevance, both qualitatively and quantitatively, of domain-specific physical activity for cardiovascular disease (CVD) subtypes in Chinese adults. Objective To assess the shape and strength of the associations of total, occupational, and nonoccupational physical activity with CVD subtypes in Chinese men and women. Design, Setting, and Participants This population-based prospective cohort study in 10 (5 urban, 5 rural) areas across China included 487 334 adults who were aged 30 to 79 (mean 51) years with no prior CVD history when enrolled from June 2004 to July 2008. Exposures Self-reported total, occupational, and nonoccupational physical activity, quantified as metabolic equivalent of task hours per day (MET-h/d) based on the type, frequency, and duration of specific activities. Main Outcomes and Measures Major vascular events (n = 36 184) and their components, including major coronary events (n = 5082), ischemic stroke (n = 25 647), intracerebral hemorrhage (n = 5252), and CVD death (n = 8437). Cox regression yielded adjusted hazard ratios for each disease that was associated with physical activity. Results Of the 487 334 study participants, 287 527 (59%) were women and the mean (SD) age was 51 (10.5) years. The overall mean (SD) total physical activity was 21.5 (12.8) MET-h/d, mainly from occupational activity, especially among men (75% vs 50% in women). Total physical activity was inversely associated with the risk of major vascular events, with the adjusted hazard ratio that compared the top vs bottom quintiles of physical activity being 0.77 (95% CI, 0.74-0.80). Throughout the range of total physical activity studied, the association with CVD with each 4 MET-h/d higher usual total physical activity (approximately 1 hour of brisk walking per day) associated with a 6% (95% CI, 5%-7%) lower risk of major vascular events, and a 9%, 5%, 6%, and 12% lower risk of major coronary events, ischemic stroke, intracerebral hemorrhage, and CVD death, respectively. The strength of the associations was similar and independent of each other for occupational and nonoccupational physical activity. However, for occupational physical activity, the associations with CVD subtypes were greatly attenuated above 20 MET-h/d, especially for intracerebral hemorrhage. The associations of total physical activity with major vascular events were similar among men and women and across different levels of sedentary leisure time but were much weaker among individuals with high blood pressure. Conclusions and Relevance Among Chinese adults, higher occupational or nonoccupational physical activity was associated with significantly lower risks of major CVD.